DEGRADABILITAS BAHAN KERING, BAHAN ORGANIK DAN NEUTRAL DETERGENT FIBER LIMBAH INDUSTRI PERTANIAN DAN PERKEBUNAN SECARA IN SACCO - Sani, Febriana Fauziyah; Nuswantara, Limbang Kustiawan; Subrata, Agung (Animal Agriculture Journal, 2012)
Utilization of waste of agricultural and plantation industry as an alternative feed source of fiber had a positive effect in supporting the development of animal husbandry. The objective of this research is to examine degradability of feed materials is seen from the soluble fraction of feed (a), potential degradable fraction of feed (b), the rate of degradation of b fraction (c value) and the degradation theory (DT) using method in sacco. Feeding materials which had been evaluated are peanut leather, coffee leather, oil cake, bagase and elephant grass. Experimental design used in this research is Completely Randomized design with 5 treatments and 3 replications. The results degradability of dry matter, organic matter and NDF showed significant effect (p<0,05) fraction a, b, c value and DT between the feed material. Feed materials of degradability affected by contents of nutrien and quality of fiber components. The waste of agricultural and plantation industry have degradability which lower than elephant grass.Key words: degradability, dry matter, organic matter, NDF, industrial waste.ABSTRAK Pemanfaatan limbah industri pertanian dan perkebunan sebagai pakan alternatif sumber serat memberikan pengaruh positif dalam menunjang perkembangan peternakan. Penelitian bertujuan untuk mengkaji degradabilitas bahan pakan yang dilihat dari fraksi pakan mudah larut (a), fraksi pakan potensial terdegradasi (b), laju degradasi fraksi b nilai (c) dan degradasi teori (DT) secara in sacco. Bahan pakan yang diujikan yaitu kulit kacang tanah, kulit buah kopi, bungkil sawit, bagase dan rumput gajah. Penelitian dilaksanakan menggunakan Rancangan Acak Lengkap dengan 5 perlakuan dan 3 ulangan. Hasil penelitian degradabilitas BK, BO dan NDF menunjukkan pengaruh nyata (p<0,05) pada fraksi a, b, nilai c dan DT antar bahan pakan. Kandungan nutrien dan kualitas komponen serat berpengaruh terhadap degradabilitas. Limbah industri pertanian dan perkebunan mempunyai degradabilitas lebih rendah dari rumput gajah.Kata kunci : Degradabilitas, bahan kering, bahan organik, NDF, limbah industri.